To Study the Difference in the Participation Level of Parents in the Education of Pakistani Students from Grade 7 To 10: Relation with Gender and Level of Studies - Ismail, Zeenat (Advances in Social Sciences Research Journal, 2017)
This study examined the relationship between parental involvement and academic performance of students from grade 7 to 10. The sample consisted of 100 literate parents who were at least high school graduates (Inter or A levels), 50 mothers and 50 fathers who were randomly selected. Before conducting the research, two things were hypothesized. Firstly, parental involvement promotes students academic success and secondly mothers tend to be more involved than fathers. Correlation was used to examine the relationship between parental involvement and academic performance. The results showed that there was a strong positive correlation of .751 between parental involvement and academic performance. Regression analysis was used to determine how strong the relationship between parental involvement and academic performance was and significance level was found out to be less than 0.05 showing significant relationship. Independent t test was used to evaluate the difference between the participation of mothers and fathers and the results showed a significant level of 0.01 which was less than 0.05 showing significant variation in the participation of mothers and fathers with mothers participation was greater than the fathers. For both the hypotheses, null hypothesis was rejected and alternate hypothesis was accepted.